2018
DOI: 10.1103/physreva.97.052332
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive recurrence quantum entanglement distillation for two-Kraus-operator channels

Abstract: Quantum entanglement serves as a valuable resource for many important quantum operations. A pair of entangled qubits can be shared between two agents by first preparing a maximally entangled qubit pair at one agent, and then sending one of the qubits to the other agent through a quantum channel. In this process, the deterioration of entanglement is inevitable since the noise inherent in the channel contaminates the qubit. To address this challenge, various quantum entanglement distillation (QED) algorithms hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…These gates inherently generate a series of errors, specifically, three types: bit flip (X-errors), phase flip (Z-errors, or phase damping), and bit-phase flip [45]. The aforementioned link will also allow a better understanding of aspects related to decoherence [14,15] in non-adiabatic environments, as well as a very common process present in all real quantum channels known as the amplitude damping [46].…”
Section: Discussionmentioning
confidence: 99%
“…These gates inherently generate a series of errors, specifically, three types: bit flip (X-errors), phase flip (Z-errors, or phase damping), and bit-phase flip [45]. The aforementioned link will also allow a better understanding of aspects related to decoherence [14,15] in non-adiabatic environments, as well as a very common process present in all real quantum channels known as the amplitude damping [46].…”
Section: Discussionmentioning
confidence: 99%
“…We note that it has been recently shown that the DE-JMPS protocol achieves the highest possible fidelity over LOCC operations when distilling a two-qubit state from two copies of a Bell diagonal state of rank two [42]. Moreover, in [41] protocols that permute Bell states in the mixture were analyzed and it was claimed that for two copies of all Bell diagonal states, DEJMPS protocol achieves the highest achievable fidelity when distilling a two-qubit state, but only among all such permuting protocols.…”
Section: B Bell Diagonal Statesmentioning
confidence: 85%
“…Furthermore, sophisticated quantum repeater protocols need to be developed for mitigating the errors introduced by the channels, which may be partly addressed through quantum error correction codes. In the absence of coding, the losses may be dealt with by heralded entanglement generation, while the error probability may be reduced by entanglement distillation (see e.g., [29]). Despite all these potential approaches, practical realization of quantum repeaters remains an open technical challenge.…”
Section: Entanglement Distribution and Quantum Networkingmentioning
confidence: 99%